2016
DOI: 10.3389/fncom.2016.00120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phase-Amplitude Coupling in Resting State Magnetoencephalographic Signals: Effect of Surrogates and Evaluation Approach

Abstract: Phase-amplitude coupling (PAC) plays an important role in neural communication and computation. Interestingly, recent studies have indicated the presence of ubiquitous PAC phenomenon even during the resting state. Despite the importance of PAC phenomenon, estimation of significant physiological PAC is challenging because of the lack of appropriate surrogate measures to control false positives caused by non-physiological PAC. Therefore, in the present study, we evaluated PAC phenomenon during resting-state magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Here, we demonstrate the typical development of PAC from 3 months through 3 years of age. This PAC occurs most prominently between alpha-beta and gamma, largely consistent with several reports of alpha-gamma PAC in resting state recordings (Roux et al, 2013;Berman et al, 2015;Gohel et al, 2016), but is also present between theta and beta, theta and gamma, and alpha and beta. We observe PAC broadly across the scalp, suggesting a relatively ubiquitous presence of cross-frequency coupling.…”
Section: Discussionsupporting
confidence: 90%
“…Here, we demonstrate the typical development of PAC from 3 months through 3 years of age. This PAC occurs most prominently between alpha-beta and gamma, largely consistent with several reports of alpha-gamma PAC in resting state recordings (Roux et al, 2013;Berman et al, 2015;Gohel et al, 2016), but is also present between theta and beta, theta and gamma, and alpha and beta. We observe PAC broadly across the scalp, suggesting a relatively ubiquitous presence of cross-frequency coupling.…”
Section: Discussionsupporting
confidence: 90%
“…A distribution against which to test the statistical significance of the MI for each channel was generated by dividing the signal into two sections and swapping amplitude and phase blocks in order to preserve the statistical properties of the data in the surrogates (Canolty et al, 2006; Foster and Parvizi, 2012; Aru et al, 2015; Gohel et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…An MI greater than zero indicates a tendency for amplitude in the high frequency signal to peak at a particular point in the phase cycle of the low frequency signal (Onslow et al, 2011 ). A distribution against which to test the statistical significance of the MI for each channel was generated by dividing the signal into two sections and swapping amplitude and phase blocks in order to preserve the statistical properties of the data in the surrogates (Canolty et al, 2006 ; Foster and Parvizi, 2012 ; Aru et al, 2015 ; Gohel et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Using Human Connectome Project (HCP) data, Gohel et al ( 2016 ) (GEA) recently reported that “resting-state MEG signals failed to exhibit ubiquitous phase-amplitude coupling (PAC) phenomenon, contrary to what has been suggested” by Florin and Baillet ( 2015 ) (FB). GEA argued that the original PAC findings by FB were driven by false positives resulting from the use of inappropriate methods.…”
Section: Introductionmentioning
confidence: 97%
“…In this commentary, we first correct GEA's mischaracterization of the approach actually used by FB. We then investigated the PAC computations in Gohel et al ( 2016 ) (GEA) and demonstrate that with FB's approach, it is actually possible to detect PAC in the Human Connectome Project (HCP) resting-state data. Finally, when making the data processing as similar as possible to GEA we still found significant PAC across large portions of the brain.…”
Section: Introductionmentioning
confidence: 99%